Spinal epidural abscess as predicting factor for the necessity of early surgical intervention in patients with pyogenic spondylitis - Jiwon Park; Sangsoo Han; Yeong Jeon; Jae-Young Hong (BMC Musculoskeletal Disorders, 2023)
Abstract Background Pyogenic spondylitis is a condition with low incidence that can lead to neurological sequelae and even life-threatening conditions. While conservative methods, including antibiotics and bracing, are considered the first-line treatment option for pyogenic spondylitis, it is important to identify patients who require early surgical intervention to prevent progressive neurologic deficits or deterioration of the systemic condition. Surgical treatment should be considered in patients with progressive neurologic deficits or deteriorating systemic condition. However, currently, there is a lack of treatment guidelines, particularly with respect to whether surgical treatment is necessary for pyogenic spondylitis. This study aims to analyze the radiological epidural abscess on MRI and clinical factors to predict the need for early surgical intervention in patients with pyogenic spondylitis and provide comprehensive insight into the necessity of early surgical intervention in these patients. Methods This study retrospectively reviewed 47 patients with pyogenic spondylitis including spondylodiscitis, vertebral osteomyelitis, epidural abscess, and/or psoas abscess. All patients received plain radiographs, and a gadolinium-enhanced magnetic resonance imaging (MRI) scan. All patients have either tissue biopsies and/or blood cultures for the diagnosis of a pathogen. Demographic data, laboratory tests, and clinical predisposing factors including comorbidities and concurrent other infections were analyzed. Results We analyzed 47 patients, 25 of whom were female, with a mean age of 70,7 years. MRI revealed that 26 of 47 patients had epidural abscesses. The surgical group had a significantly higher incidence of epidural abscess than the non-surgical group (p = 0.001). In addition, both CRP and initial body temperature (BT) were substantially higher in the surgical group compared to the non-surgical group. There was no significant difference between the surgical group and the non-surgical group in terms of age, gender, comorbidities, and concurrent infectious disorders, as well as the number of affected segments and affected spine levels. However, the surgical group had lengthier hospital stays and received more antibiotics. Conclusion The presence of an epidural abscess on MRI should be regarded crucial in the decision-making process for early surgical treatment in patients with pyogenic spondylitis in order to improve clinical outcomes.